Methodological Proposal for the Identification and Characterization of Industrial Heritage Landscapes - Alba-Dorado, María Isabel; Meira da Silva, Milena (Universidad de la Costa - CUC, 2025)
The industrial heritage landscape constitutes a complex phenomenon whose study has been addressed belatedly by the scientific community in general. This has given rise to a situation of conceptual and methodological insufficiency to undertake its study, which forces us to rethink the ways in which these have been approached until now and to develop a methodological framework that takes into account their specificity. In this sense, this article aims to design a methodology for the identification and characterization of these landscapes based on their heritage and cultural considerations. The method used contem- plates a conceptual approach to the industrial heritage landscape, a study of the different dimensions that characterize it and the design of methodological keys for its identification and characterization. Based on the results obtained, an explicit methodological proposal has been made that addresses the study of these landscapes from a holistic, open, and integrative approach.

El paisaje del patrimonio industrial configura un fenómeno complejo cuyo estudio ha sido abordado tardíamente por la actividad científica en general. Esto ha dado lugar a una situación de insuficiencia conceptual y metodoló- gica para acometer su estudio que obliga a replantear los modos en los que hasta el momento éstos han sido abordados y elaborar un marco metodológico que contemple su especificidad. En este sentido, este artículo tiene como objetivo diseñar una metodología para la identificación y caracterización de estos paisajes a partir de su consideración patrimonial y cultural. El método empleado contempla una aproximación conceptual al paisaje del patrimonio industrial, un estudio de las distintas dimensiones que lo caracterizan y el diseño de unas claves metodológicas para su identificación y caracterización. En base a los resultados obtenidos, se ha explicitado una propuesta metodo- lógica que aborda el estudio de estos paisajes a partir de un enfoque holístico, abierto e integrador.
Keywords: Arquitectura del paisaje; Industrial heritage; Caracterización paisajística